The Development Concept of Organic Village Tourism in Karanganyar - Wisnu Setiawan; Andika Saputra (Warta LPM, 2022)
The ratification of Law No. 6 of 2014 concerning the development of rural environments has had a significant impact on the development of villages in Indonesia, among others, through the concept of a tourist village. Several villages have succeeded in developing the concept of tourism in a rural environment in an authentic and sustainable manner, while on the other hand, several villages seem to have followed the existing trend without carefully looking at the local environmental context. This paper presents the semi research community service activity carried out to understand better this phenomenon in Kampung Ngampel, Gentungan Village, Mojogedang District, Karanganyar Regency which is currently developing the concept of Organic Village Tourism. The activity is carried out with a focus on two things: developing the initial concept of tourism areas and training in tourism area management. This service activity was carried out with the full support of the community and resulted in several ideas. The final results of the training activities provide a clearer picture to the community regarding contextual and sustainable tourism village management.